Feasibility of exercise therapy for children with asthma: a meta-analysis - Zhou, Linyuan; Xu, Haofu (Frontiers in Cell and Developmental Biology, 2023)
Asthma is one of the most common chronic diseases worldwide among adults and children. Pharmacological and non-pharmacological treatments are available. Non-pharmacological treatments generally refer to physical therapies, including exercise therapy, respiratory exercise, and muscle training. However, the three are often lumped together and do not distinguish between adults and children. Therefore, we focused on the effects of both recreational and social exercise therapy on childhood asthma. By analyzing and comparing the effects of different exercise intensity, exercise mode and other exercise interventions on children's lung function and quality of life, we found that swimming and aerobic exercise could effectively enhance the pulmonary function index and immune system in asthmatic children, improve the quality of life and exercise ability of asthmatic children and effectively reduce the BMI of asthmatic children. These findings may provide practical reference and control means for the treatment of children asthma.